Students' Technology Preference and Computer Technology Applications in the Teaching and Learning of Physics Modules at the University Undergraduate Level in South Africa during the COVID-19 Pandemic - Patrick Mukumba; Ngwarai Shambira (MDPI AG, 2022)
This research aims to establish students' technology preferences and computer technology applications in the teaching and learning of university physics modules during the COVID-19 pandemic. The proposed objectives were (a) to establish students' technology preferences in physics modules for 2nd and 3rd-year undergraduate level students; (b) to establish students' hardware technology preferences and hardware technology they own; (c) to determine relationships between technology preferences using Pearson's correlation coefficient and (d) to determine the effectiveness of the integration of computer technology applications in the lecturer's teaching and learning of physics modules. Forty-one students (58.5% male and 41.5% female) participated. The questionnaire data was examined utilising descriptive and inferential statistics. Based on the findings of this study, integrating technology in tertiary physics education is recommended as it may enhance the comprehension of abstract and difficult physics concepts.